Sultan Abdul Qahir dalam Pengembangan Islam di Bima - rahmat, rahmat; nurwahidah, nurwahidah (Rihlah: Jurnal Sejarah dan Kebudayaan, 2019)
Regarding Sultan Abdul Qahir is very interesting because since he was appointed by the king of Gowa and embraced Islam became the beginning of the development of Islam in Bima. Education as the main channel of Islamization is carried out in households raised by parents and ulemas, religious teachers such as the art of reading barzanji which is still valid in the villages. Carving, seen in the pulpit of the mosque, heirloom keris carved in such a way that it looks very beautiful grooves. Hadra, which is a kind of Islamic art in the form of dhikr in Arabic while shaking the body according to the tambourine rhythm which is done by sitting also standing. The second channel is a fairly successful propaganda method carried out by preachers is by approaching the community such as, adjusting to the situation and conditions of the people who hold fast to the old beliefs of Animism and Dynamism. The method of preaching like the one above is to look at the situation and condition of the community indeed has been exemplified by the Prophet Muhammad. Mengenai Sultan Abdul Qahir sangat menarik karena sejak Ia dilantik oleh raja Gowa dan memeluk Islam menjadi awal perkembangan Islam di Bima. Pendidikan sebagai saluran utama islamisasi dilakukan dalam rumah tangga yang diasuh oleh orang tua dan para ulama. Pelajaran untuk didikan anak dilingkungan kesultanan Bima waktu itu selain belajar agama Islam (rukun, iman, rukun Islam, thaharah, adab), juga untuk meyiapkan putra-putrinya secara khsusus untuk tujuan-tujuan dan tanggung jawab yang dihadapinya dalam kehidupan mendatang. Kegiatan pendidikan Islam di istana sebagaimana yang diuraikan di atas membawa pengaruh yang luas dikalangan masyrakat, yang berdatangan untuk belajar agama Islam dan berguru kepada mubalig/guru di istana untuk beberapa lama. Saluran kedua dengan cara pendekatan kepada masyarakat seperti, penyesuaian diri dengan situasi dan kondisi masyarakat yang berpegang teguh pada kepercayaan lama Animisme dan Dinamisme. Metode dakwah yang seperti tersebut diatas adalah dengan melihat situasi dan kondisi masyarakat memang sudah dicontohkan oleh Nabi Muhammad saw.